Comparative Analysis of Static Axial Compressive Load Test (Reaction Test) with Kentledge Pile in the Construction of TLT Tower 1 Supporting Facility Building - Bernolpus Tingge; Deri Febriansyah; Dony Setyadi Laksono; KMS. M. Rama Perwira; Rud Nokeo Alkindi (International Journal Labs, 2025)
The foundation plays a crucial role in building structures by transferring loads from the superstructure to the stable soil layer beneath. Ensuring the adequacy of the foundation's load-bearing capacity is critical, and Static Axial Compressive Load Testing on foundation piles is essential to verify whether the piles can support the intended design loads. This study compares two commonly used static load test methods: the reaction pile test and the kentledge test, within the context of the TLT Tower 1 Supporting Facility Building Construction Project. The research aims to evaluate these methods based on implementation efficiency, result accuracy, cost-effectiveness, and worksite safety. A comparative analysis approach was employed, utilizing both test methods on the project site to assess their performance under field conditions. The results demonstrate that both methods possess distinct advantages and limitations. The reaction pile test method offers higher accuracy and operational efficiency under certain conditions, particularly in constrained site environments. Conversely, the kentledge test method is generally more cost-effective but may present limitations in terms of load precision and logistical complexity. These findings suggest that the selection of an appropriate static load testing method should be based on specific site conditions, testing objectives, and budgetary considerations. The study recommends a project-specific approach to foundation pile testing, aligning method selection with the unique requirements of the construction project.